2018
DOI: 10.1103/physrevd.98.064014
|View full text |Cite
|
Sign up to set email alerts
|

Upper bound on the gravitational masses of stable spatially regular charged compact objects

Abstract: In a very interesting paper, Andréasson has recently proved that the gravitational mass of a spherically symmetric compact object of radius R and electric charge Q is bounded from aboveIn the present paper we prove that, in the dimensionless regime Q/M < 9/8, a stronger upper bound can be derived on the masses of physically realistic (stable) self-gravitating horizonless compact objects: M < R 3 + 2Q 2 3R .

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 27 publications
(99 reference statements)
0
13
0
Order By: Relevance
“…However, an interesting problem was suggested in [41], i.e., it was posed a question if the addition of some characteristics of horizonless object could improve the upper bound on its gravitational mass. The refinement of the bounds derived in [40] was presented in [41]. On the other hand, geodesic motion determines important features of the spacetime and objects in it.…”
Section: Tov Equationmentioning
confidence: 99%
“…However, an interesting problem was suggested in [41], i.e., it was posed a question if the addition of some characteristics of horizonless object could improve the upper bound on its gravitational mass. The refinement of the bounds derived in [40] was presented in [41]. On the other hand, geodesic motion determines important features of the spacetime and objects in it.…”
Section: Tov Equationmentioning
confidence: 99%
“…And it was also proved that the innermost light ring provides the fastest way to circle a central black hole as measured by observers at the infinity [21][22][23]. Moreover, the existence of stable light rings suggests that the central compact stars may suffer from nonlinear instabilities [24][25][26][27][28][29][30]. And unstable light rings can be used to determine the characteristic resonances of black holes [31][32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 96%
“…It was suggested that the characteristic resonances of black holes can be interpreted as null particles trapped at the unstable circular orbit and slowly leaking out [23][24][25][26][27][28][29][30]. In the regular ultra-compact star spacetime, the existence of stable circular null geodesics could trigger nonlinear instabilities due to that massless fields can pile up on the stable null obit [31][32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%